2016
DOI: 10.1002/gcc.22348
|View full text |Cite
|
Sign up to set email alerts
|

Frequent BCOR aberrations in extranodal NK/T‐Cell lymphoma, nasal type

Abstract: Extranodal natural killer/T cell lymphoma (ENKTL) is a rare subtype of lymphoma. Recurrent mutations in the JAK-STAT pathway, recently reported in ENKTL cases, are interesting in terms of both pathogenesis and inhibitor therapy. However, the frequencies of these mutations are low and variable among reports, and other pathognomonic mutations in ENKTL remain to be elucidated. In the present study, targeted capture sequencing of 602 cancer-related genes from 25 frozen ENKTL samples was performed, 11 of which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 47 publications
4
114
1
1
Order By: Relevance
“…Another study of a Chinese population revealed an similar frequency of 12% (three of 25) [65]. This frequency was found to be higher in Korea (26.4%, nine of 34) [66] and slightly lower in Japan (8%, two of 25) [18]. STAT3 mutations were found to occur at several (Fig.…”
Section: Stat3mentioning
confidence: 79%
See 4 more Smart Citations
“…Another study of a Chinese population revealed an similar frequency of 12% (three of 25) [65]. This frequency was found to be higher in Korea (26.4%, nine of 34) [66] and slightly lower in Japan (8%, two of 25) [18]. STAT3 mutations were found to occur at several (Fig.…”
Section: Stat3mentioning
confidence: 79%
“…Traditional Sanger sequencing technology revealed very high mutation frequencies of TP53 in NKTCL, specifically, 63% (17 of 27 cases) in Indonesia [13], 40% (eight of 20 cases) in China [14], 18.9% (six of 32 cases) and 62% (36 of 58 cases) in Japan [15,16], and 31% (13 of 42 cases) in Korea [15]. These high frequencies were detected using polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP) followed by direct sequencing.…”
Section: Tp53mentioning
confidence: 99%
See 3 more Smart Citations